# Suppose Y Is A Function Of X, F(x,y) = 0, And Fy D

 EliteHead89 From: USPosts: 18Votes: 18 Suppose y is a function of x, F(x,y) = 0, and Fy does not = 0. Show that dy/dx = - Fx/Fy iGenius From: USPosts: 3Votes: 12 F(x,y) = 0 --> dF=0--> Fxdx+Fydy=0 --> Fxdx=-Fydy --> (dy/dx)=-Fx/Fy  Anonymous From: -Posts: -Votes: - F(x,y) = 0 dF = 0 Fx dx + Fy dy = 0 Fxdx = - Fydy Since,Fy != 0 (dy/dx)=-Fx/Fy Hence,proved  sam mayo From: USPosts: 15Votes: 60 DF = Fx * dx + Fy * dy dF/dx = Fx + Fy*dy/dx F(x,y) = 0 ==> dF/dx = 0 ∴ 0=Fx + Fy*dy/dx and dy/dx = - Fx/Fy  Anonymous From: -Posts: -Votes: - DF = Fx*dx + Fy*dy or, dF/dx = Fx + Fy*dy/dx since, F(x,y) = 0 therefore, dF/dx = 0 or, Fx + Fy*dy/dx = 0 or, dy/dx = -Fx/Fy  BrainyBrainy From: USPosts: 8Votes: 24 DF = Fx * dx + Fy * dy dF/dx = Fx + Fy*dy/dx F(x,y) = 0 ==> dF/dx = 0 ? 0=Fx + Fy*dy/dx and dy/dx = - Fx/Fy hence proved  TheGreatMonkey From: USPosts: 8Votes: 16 DF = Fx * dx + Fy * dy dF/dx = Fx + Fy*dy/dx F(x,y) = 0 ==> dF/dx = 0 ? 0=Fx + Fy*dy/dx and dy/dx = - Fx/Fy HENCE PROVED  Anonymous From: -Posts: -Votes: - DF = Fx*dx + Fy*dy =>F/dx = Fx + Fy*dy/dx but f(x,y)=0 so df/dx=0 =>Fx + Fy*dy/dx = 0 dy/dx = -Fx/Fy (proved)  Enter 